H-ferritin and proinflammatory cytokines are increased in the bone marrow of patients affected by macrophage activation syndrome. (20th October 2017) - Ruscitti, P; Cipriani, P; Di Benedetto, P; Liakouli, V; Berardicurti, O; Carubbi, F; Ciccia, F; Guggino, G; Triolo, G; Giacomelli, R
Summary: Macrophage activation syndrome (MAS) is hyperinflammatory life-threatening syndrome, associated typically with high levels of serum ferritin. This is an iron storage protein including heavy (H) and light (L) subunits, categorized on their molecular weight. The H-/L subunits ratio may be different in tissues, depending on the specific tissue and pathophysiological status. In this study, we analysed the bone marrow (BM) biopsies of adult MAS patients to assess the presence of: (i) H-ferritin and L-ferritin; (ii) CD68 + /H-ferritin + and CD68 + /L-ferritin + ; and (iii) interleukin (IL)-1β, tumour necrosis factor (TNF) and interferon (IFN)-γ. We also explored possible correlations of these results with clinical data. H-ferritin, IL-1β, TNF and IFN-γ were increased significantly in MAS. Furthermore, an increased number of CD68 + /H-ferritin + cells and an infiltrate of cells co-expressing H-ferritin and IL-12, suggesting an infiltrate of M1 macrophages, were observed. H-ferritin levels and CD68 + /H-ferritin + cells were correlated with haematological involvement of the disease, serum ferritin and C-reactive protein. L-ferritin and CD68 + /L-ferritin + cells did not correlate with these parameters. In conclusion, during MAS, H-ferritin, CD68 + /H-ferritin + cells and proinflammatory cytokines were increased significantly in the BM inflammatory infiltrate, pointing out a possible vicious pathogenic loop. To date, H-ferritin and CD68 + /H-ferritin + were associated significantly with haematological involvement of the disease, suggesting biomarkers assessing severity of clinical picture. Graphical Abstract: